SPA TIO-TEMPORAL CHARACTERIZATION OF MODIFIED STARCH SPRAY IN AMBIENT AND FLUIDIZED BED COATING ENVIRONMENT - NAZ, MUHAMMAD YASIN (2014)
The spray coating technology has demonstrated great potential for slow release fertilizers industry. Better understanding of the key spray parameters can benefit both environment and low cost coating processes. However, the hydraulic spray jet breakup of the Non-Newtonian coating solutions is still a complex phenomenon and very little known. Aim of the given research was to study the time based spray evolution of the coating solutions from three full cone nozzles namely FC-2, FC-3 and FC-3.5, under ambient and fluidized bed coating conditions. To meet the objective, the imaging and DualPDA studies were conducted on developing sprays of five starch-urea-borate compositions (S 0, S1, S2 S3 and S4) at elevated temperatures and pressures. The unheated coating solutions did not exhibit any jet breakup over time.